A Pilot Study of Monotherapy with a Non-Vitamin K-Antagonist Oral Anticoagulant following Watchman Left Atrial Appendage Closure in Patients with Non-Valvular Atrial Fibrillation. Issue 4 (3rd July 2020) - Price, Matthew J.; Lerner, David; Rastogi, Ashish; Romero, Steven; Smith, Michael R.; Rubenson, David; Funk, Jessica; Janzcyk, Gwen; Edwards-Mobley, Monique; Wheeler, Carmen; Gibson, Douglas
ABSTRACT: Background: The optimal medical therapy early after left atrial appendage closure (LAAC) is not well defined. A regimen that prevents thromboembolic events and device-related thrombus (DRT) while minimizing bleeding would be of clinical importance. Methods: This was a single-center, prospective, open-label study. Patients undergoing commercially indicated WATCHMAN LAAC were treated with edoxaban monotherapy (i.e., without concomitant aspirin) for 6 weeks, at which time imaging and clinical follow-up were performed. A clinical events committee evaluated adverse events and at least 2 echocardiographers adjudicated follow-up imaging. The primary clinical endpoint was the composite of death, stroke, systemic embolism, or GUSTO-defined moderate or severe/life-threatening bleeding. The key imaging endpoint was DRT. Results: A total of 75 patients were enrolled. The mean patient age was 79.6 ± 8.0 years, the mean CHA2 DS2 VASc score was 4.5 ± 1.3, the mean HAS-BLED score was 2.6 ± 0.8, and 46 patients (61.3%) had experienced a prior bleed. At a mean follow-up duration of 43 ± 8 days, the primary endpoint occurred in 1 patient (1.3%) as a result of a single GUSTO moderate bleed. DRT was observed in 1 patient (1.3%). Conclusions: In this pilot study, monotherapy with edoxaban after WATCHMAN LAAC appeared safe and was associated with an acceptable rate of major bleeding and DRT. Whether a post-implant regimen of non-vitamin K oral anticoagulant monotherapy may be an alternative to the currently approved regimen of warfarin and aspirin, particularly in patients at high bleeding risk, should be further evaluated in a large, adequately powered trial.